2020
DOI: 10.1101/2020.02.11.20022061
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting loss of independence and mortality in frontotemporal lobar degeneration syndromes

Abstract: Objective To test the hypothesis that in syndromes associated with frontotemporal lobar degeneration, behavioural impairment predicts loss of functional independence and motor clinical features predict mortality, irrespective of syndrome subtype. Method We used a transdiagnostic approach to survival in an epidemiological cohort, testing the association between clinical features, independence and survival in patients with clinical diagnoses of behavioural variant frontotemporal dementia (n=64), non-fluent var… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Behavioural change is a common feature of the syndromes associated with frontotemporal lobar degeneration (FTLD) pathology, including behavioural variant frontotemporal dementia (bvFTD) and progressive supranuclear palsy (PSP) ( Gerstenecker et al , 2013 ; Bang et al , 2015 ; Lansdall et al , 2017 ; Murley et al , 2020 a ). This is associated with loss of functional independence ( Agarwal et al , 2019 ; Murley et al , 2020 b ) and increased mortality ( Lansdall et al , 2019 ) in both disorders. Better treatment of behavioural symptoms might therefore improve both functionally independent survival and quality of life for patients and their families.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioural change is a common feature of the syndromes associated with frontotemporal lobar degeneration (FTLD) pathology, including behavioural variant frontotemporal dementia (bvFTD) and progressive supranuclear palsy (PSP) ( Gerstenecker et al , 2013 ; Bang et al , 2015 ; Lansdall et al , 2017 ; Murley et al , 2020 a ). This is associated with loss of functional independence ( Agarwal et al , 2019 ; Murley et al , 2020 b ) and increased mortality ( Lansdall et al , 2019 ) in both disorders. Better treatment of behavioural symptoms might therefore improve both functionally independent survival and quality of life for patients and their families.…”
Section: Introductionmentioning
confidence: 99%
“…Such symptomatic treatment is a priority given the severe sequelae of cognitive impairment in FTLD. 7,23,26 However, it remains unclear to what extent our findings reflect a potentially reversible deficit of synaptic glutamate. MRS measures the total pool of unbound glutamate, involved in neuron and glia metabolism, protein synthesis and neurotransmission.…”
Section: Discussionmentioning
confidence: 89%
“…Our cohort has limited pathological confirmation of the diagnosis but clinicopathological correlations in the PIPPIN study as whole match those found elsewhere. 6,7 Therefore, while spectroscopy may be a valuable measure of early disease and/or disease progression it is unlikely to differentiate FTLD syndromes according to their underlying proteinopathies. Third, due to small numbers we grouped non-fluent, semantic and logopenic variants of PPA together, although these sub-groups have different clinical and neuropathological features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation